Prediction of dispersion and attenuation on elastic wave velocities in partially saturated rock based on the fluid distribution obtained from three-dimensional (3D) micro-CT images - Sun, Chao; Fortin, Jérôme; Tang, Genyang; Wang, Shangxu (Frontiers in Earth Science, 2023)
Elastic wave attenuation in partially saturated porous rock is primarily due to wave-induced fluid flow, which arises from the contrast in compressibility between air and water and is influenced by the water distribution within the rock. We propose a method for constructing a numerical model that predicts mesoscopic dispersion and attenuation. Initially, we employ fluid distribution data sourced from 3D X-ray Computed Tomography images to construct the numerical model, utilizing Biot’s poroelastic equations as the governing equations. Subsequently, we implement the finite element method to derive solutions for the numerical model. Our focus is centered on two key challenges: i) reducing memory cost, and ii) efficiently handling element intersection during the meshing process. The solutions illustrate the evolution of fluid pressure distribution and the frequency-dependent advancement of the elastic moduli, coupled with their corresponding attenuation. Ultimately, we compare these numerical predictions with previously published experimental data from a study on partially saturated Indiana limestone. The considerable agreement between our numerical results and the experimental data confirms the validity of our method, which crucially incorporates the actual fluid distribution (captured from 3D CT images) as a vital input.